2022
DOI: 10.34133/2022/9781758
|View full text |Cite
|
Sign up to set email alerts
|

Structural Comparison and Drug Screening of Spike Proteins of Ten SARS-CoV-2 Variants

Abstract: SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) has evolved many variants with stronger infectivity and immune evasion than the original strain, including Alpha, Beta, Gamma, Delta, Epsilon, Kappa, Iota, Lambda, and 21H strains. Amino acid mutations are enriched in the spike protein of SARS-CoV-2, which plays a crucial role in cell infection. However, the impact of these mutations on protein structure and function is unclear. Understanding the pathophysiology and pandemic features of these SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Targeting pyroptosis or apoptosis induced by inflammasomes is suggested to be a promising strategy in COVID-19 and other disease treatment [ 1 , 13 , 20 , 40 ]. Focusing on exploring the efficient control strategy of the transducers is therefore a significant issue [ 41 ]. Our results clearly demonstrate that only the decrease of caspase-1 and GSDMD levels can individually switch death modes from pyroptosis to apoptosis ( Figure 3(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting pyroptosis or apoptosis induced by inflammasomes is suggested to be a promising strategy in COVID-19 and other disease treatment [ 1 , 13 , 20 , 40 ]. Focusing on exploring the efficient control strategy of the transducers is therefore a significant issue [ 41 ]. Our results clearly demonstrate that only the decrease of caspase-1 and GSDMD levels can individually switch death modes from pyroptosis to apoptosis ( Figure 3(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…They have found that the AlphaFold2 models are entirely consistent with the experimental RDC data for most proteins. Yang et al have adopted AlphaFold2 to predict the structures of S proteins according to the sequences of the mutants and successfully predicted the S proteins of 10 major variants of SARS-CoV-2, including the Original, Alpha, Beta, Gamma, Delta, Epsilon, IOTA, Kappa, Lambda and 21H strains [56] . Gupta et al have combined the cryo-EM with AlphaFold2 to obtain the atomic model of full-length SARS-COV-2 non-structural protein 2 (NSP2) [57] , which reveals a highly-conserved zinc ion-binding site, suggesting a role for NSP2 in RNA binding.…”
Section: Basic Steps Of Sbddmentioning
confidence: 99%
“…The structures of most of the monkeypox virus proteins remain unknown, knowledge of which would significantly enhance our understanding of the molecular mechanisms underlying critical viral processes such as viral entry and replication. AlphaFold2 is a powerful open-source computational approach developed to help predict protein structures 3 , which has been used successfully in acquiring accurate protein structures of the human and SARS- CoV-2 proteomes 4 , 5 , 6 .…”
mentioning
confidence: 99%
“…AlphaFold2 is a powerful open-source computational approach developed to help predict protein structures, 3 which has been used successfully in acquiring accurate protein structures of the human and SARS-CoV-2 proteomes. [4][5][6] Here, we used AlphaFold2 to predict the protein structures of the reference monkeypox virus proteome (Uniprot ID: UP101269 7 ), yielding a total of 186 highly accurate protein structures (Supplemental Table S1). The mean predicted Local Distance Difference Test (pLDDT) values of 156 of the 186 proteins are above the threshold of 70, which suggests that the predicted structures for these proteins are highly accurate ( Fig.…”
mentioning
confidence: 99%